Interactive Video Learning Media Based on the Problem Based Learning (PBL) Model in the Circulatory System - Waltriandi, Yandri; Mellisa (Journal Of Biology Education Research (JBER), 2025)
The use of interactive video media in learning plays an important role because it can increase active student engagement, provide a more meaningful learning experience, and facilitate the understanding of abstract concepts. In addition, the application of the Problem Based Learning (PBL) learning model is also effective in developing students' critical and collaborative thinking skills through contextual problem solving. The circulatory system material was chosen because this topic requires an understanding of complex concepts and is directly related to health and daily life. This study aims to develop interactive learning videos based on the PBL model for the science subject, focusing on the circulatory system topic for junior high school students. The development model used is Analysis, Design, Development, Implementation, Evaluation (ADDIE). Data were obtained through expert validation, observation, questionnaires, and limited trials. The validation results from media experts, material experts, and learning experts with a very valid category. The student response is categorized as very appropriate. Thus, the developed interactive video media is declared valid, practical, and effective in improving conceptual understanding and student learning motivation. This media can help students more easily understand the relationship between the circulatory system and everyday life.